Supervision and autonomy of ophthalmology residents in the outpatient Clinic in the United States: a survey of ACGME-accredited programs - Singman, Eric L. (BMC Med Educ, 2017)
BACKGROUND: The development and demonstration of incremental trainee autonomy is required by the ACGME. However, there is scant published research concerning autonomy of ophthalmology residents in the outpatient clinic setting. This study explored the landscape of resident ophthalmology outpatient clinics in the United States. METHODS: A link to an online survey using the QualtricsTM platform was emailed to the program directors of all 115 ACGME-accredited ophthalmology programs in the United States. Survey questions explored whether resident training programs hosted a continuity clinic where residents would see their own patients, and if so, the degree of faculty supervision provided therein. Metrics such as size of the resident program, number of faculty and clinic setting were also recorded. Correlations between the degree of faculty supervision and other metrics were explored. RESULTS: The response rate was 94%; 69% of respondents indicated that their trainees hosted continuity clinics. Of those programs, 30% required a faculty member to see each patient treated by a resident, while 42% expected the faculty member to at least discuss (if not see) each patient. All programs expected some degree of faculty interaction based upon circumstances such as the level of training of the resident or complexity of the clinical situation. 67% of programs that tracked the contribution of the clinic to resident surgical caseloads reported that these clinics provided more than half of the resident surgical volumes. More ¾ of resident clinics were located in urban settings. The degree of faculty supervision did not correlate to any of the other metrics evaluated. CONCLUSIONS: The majority of ophthalmology resident training programs in the United States host a continuity clinic located in an urban environment where residents follow their own patients. Furthermore, most of these clinics require supervising faculty to review both the patients seen and the medical documentation created by the resident encounters. The different degrees of faculty supervision outlined by this survey might provide a useful guide presuming they can be correlated with validated metrics of educational quality. Finally, this study could provide an adjunctive resource to current international efforts to standardize ophthalmic residency education. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-017-0941-0) contains supplementary material, which is available to authorized users.